The evolution of diversity in the structure and function of artificial organisms - Fernández-Rodríguez, Jose David (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2012)
Life on Earth has been shaped by evolutionary processes into a marvelous diversity of form and function, at all levels from melecules to ecosystems. It can be expected that no single conceptual framework ca encompass all the aspects of the evolution of diversity. This thesis explores this question from three different points of view: the role of developmental processes, the role of evolutionary dynamics, and the interplay between the body's control system.
Keywords: Biología computacional; Evolutionary computation; Artificial development; Tensegrity; L-system; Morphological computation